Die vermyding van etniese spanning en konflik in Suid-Afrika: Wat kan Paulus se ervaring ons leer? - Cromhout, Markus (HTS teologiese studies, 2011)
Avoiding ethnic tension and conflict in South Africa: What can we learn from Paul’s experience?The dream of a ‘rainbow nation’ in South Africa appears to be on the wane as ethnic tension and conflict seem to simmer just beneath the surface. This article investigates Paul’s approach to the issue of ethnic identity with reference to ethnicity and social identity theory. Initially, Paul adopted a radical approach, which basically rendered ethnic identity irrelevant. However, he came to realise that ethnic differences need to be accommodated within the group of Jesus followers. The article applies these insights in calling for strong, moral, visionary and discerning leadership in South Africa.